2006
DOI: 10.1080/00103620600817572
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Fertility Assessment of Intensively Farmed Areas of Catchments Draining to the Great Barrier Reef World Heritage Area; 1: Soil Phosphorus Status

Abstract: Australia's reef water quality protection plan has a key objective: "reduce the load of pollutants from diffuse sources in the water entering the Reef." This article reports on a survey to assess the contemporary phosphorus (P) status of fertilized cropping soils across 21 catchments in coastal Queensland, Australia. The survey focused on surface soils from cane farms, vegetable and subtropical/tropical fruit tree sites. There were sampling depth effects on P levels in sugar and fruit tree sites (lower with de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…These benchmarks therefore imply that surface orthophosphate soil concentrations at the study site were ~1.5-2.25-fold higher than requirements for the optimum yield of macadamia. Soil surveys have found that excessive surface concentrations of orthophosphate are not uncommon in contemporary treecropping enterprises in coastal Queensland, as evidenced by a majority of the survey sites which had topsoil phosphate concentrations >60 mg/kg (Rayment and Bloesch 2006).…”
Section: Temporal Variation In Soil Phosphate Within Tree Beds At The...mentioning
confidence: 99%
“…These benchmarks therefore imply that surface orthophosphate soil concentrations at the study site were ~1.5-2.25-fold higher than requirements for the optimum yield of macadamia. Soil surveys have found that excessive surface concentrations of orthophosphate are not uncommon in contemporary treecropping enterprises in coastal Queensland, as evidenced by a majority of the survey sites which had topsoil phosphate concentrations >60 mg/kg (Rayment and Bloesch 2006).…”
Section: Temporal Variation In Soil Phosphate Within Tree Beds At The...mentioning
confidence: 99%